Practicality of Project-Based Learning-Based Electronic Student Worksheets for Teaching Biotechnology to Senior High School Students - Prasetyo, Farid Agung; Hajar, Ibnu; Hidayati, Nurkhairo (Jurnal Paedagogy, 2026)
This study aims to describe the level of practicality of a Project-Based Learning (PjBL)–based electronic student worksheet (e-LKPD) on biotechnology material for tenth-grade senior high school students. The study employed a Research and Development (R&D) approach adapted from the Plomp model, with a focus on the assessment phase, particularly the practicality evaluation. The research was conducted in two schools, namely SMA Negeri 1 Tambang and SMA Negeri 2 Kampar Kiri Tengah, in Riau Province, Indonesia. Data were collected from 49 students, two biology teachers, and two observers using practicality questionnaires, learning implementation observation sheets, interview guidelines, and documentation. The data were analyzed using both quantitative and qualitative descriptive techniques. The results indicate that the practicality level of the e-LKPD, as assessed by students, reached an average score of 83%, categorized as very practical, while teachers’ assessments reached 86%, also categorized as very practical. The implementation of learning using the e-LKPD achieved 100% (very good category) based on student responses and 95% (very good category) based on teacher responses. Observers reported an average implementation score of 94%, categorized as very good. These findings suggest that the PjBL-based e-LKPD is practical for use in biotechnology learning at the senior high school level. Furthermore, it supports the development of 21st-century skills, including critical thinking, creativity, and collaboration, through project-based learning activities.